Challenges Facing the Nursing Profession in Saudi Arabia: An Integrative Review - Alsadaan, Nourah; Jones, Linda K.; Kimpton, Amanda; DaCosta, Cliff (Nursing reports (Pavia, Italy), 2021)
There is a paucity of recent literature identifying the issues facing the nursing profession in Saudi Arabia. The aim of this integrative review is to highlight the ongoing challenges facing the nursing profession in Saudi Arabia despite attempts to make a difference and suggests recommendations for the future. Literature published from 2000 to 2020, inclusive, relevant for nursing challenges in Saudi Arabia was accessed and reviewed from multiple sources. In Saudi Arabia, inadequate numbers of Saudi nurses have prompted an increase in recruitment of expatriate nurses. This has created its own issues including, retention, lack of competency in English and Arabic, as well as Arabic cultural aspects, insufficient experience, and a high workload. The result is job dissatisfaction and increased attrition as these nurses prefer to move to more developed countries. For national nurses, the issues are the need to recruit more and retain these nurses. There are a range of cultural factors that contribute to these issues with national nurses. There is a need to improve the image of nursing to recruit more Saudi nurses as well as addressing issues in education and work environment. For expatriate nurses there is a need for a better recruitment processes, a thorough program of education to improve knowledge and skills to equip them to work and stay in Saudi. There is also a need for organizational changes to be made to increase the job satisfaction and retention of nurses generally. Healthcare in Saudi Arabia also needs leaders to efficiently manage the various issues associated with the nursing workforce challenges.